A qualitative analysis of the main threats to Asian elephant conservation - Lee, Ee Ling; Ariffin, Mariani; Abd Manaf, Latifah (Asian Elephant Specialist Group, 2016)
In this study we identified the main threats to the conservation of Asian elephants and discuss their causes and implications. Primary data from interviews and secondary data from published articles were gathered and analysed using inductive and deductive thematic content analysis assisted by NVivo 10. Our results indicate that the three main threats for the species are human-elephant conflict, habitat loss, and poaching. The conversion of forests into plantations and human-dominated areas, including infrastructure developments, are the primary causes for human-elephant conflict and habitat loss. Meanwhile, the high demand and monetary return from ivory trade are the primary causes to illegal poaching.